Analisis Kearifan Lokal Gamelan (Saron) pada Konsep Fisika Gelombang dan Bunyi - Damarsha, Adrian Bagas; Niza, Alvin Khoirun; Fitriyah, Lailatul; Deta, Utama Alan; Suliyanah, Suliyanah; Saputra, Oka (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
This study aims to analyze the relationship between the local wisdom of gamelan (saron) and the concept of physics on sound waves and to analyze the effect of the material in gamelan (saron) on sound scales and sound resonance. In this article the experimental method used is qualitative research, with conducting structured interviews with informants, and analyzing the data obtained. In this article, the physics concept contained in the gamelan (saron) is obtained, namely the concept of sound waves. In gamelan (saron) when hitting a blade after being hit, the saron blades are dipitet so that the sound produced is not humming and the tone produced is clear. This is also related to the material for making gamelan (saron) which affects the sound produced or sound quality. Each blade or scale on the saron is different from the thinnest to the thickest. From this article it is concluded that gamelan (saron) is related to physics learning, namely sound waves. The materials and ladder blades in the gamelan (saron) affect the quality of the sound produced. Gamelan (saron) teaches Javanese cultural values ??and as a benchmark for the height or civilization of a nation.